Bridging technology and health: A panel analysis of internet use, mobile subscriptions, and health spending in G7 - Funda Kaya; Mamunur Rashid; Miguel Angel Esquivias; Salma Akter; Sumit Chandra Podder (Social Sciences and Humanities Open, 2025)
Technology's impact on public health demands scrutiny, as health disparities persist even in G7 countries. The purpose of this study is to examine how Internet use, mobile subscriptions, GDP per capita, and health expenditure affect life expectancy, as well as to investigate correlations between these technical and socioeconomic variables and health outcomes. Panel data from 1997 to 2021 were used, and long-term correlations were examined using the fixed effect and PMG-ARDL methods. The findings demonstrated that Internet use and mobile subscriptions have a favorable impact on life expectancy by improving the exchange and delivery of healthcare information. Also, since income increases access to and investment in healthcare, higher GDP per capita is associated with longer life expectancy. Meanwhile, health expenditures had mixed impacts, with a negative and significant coefficient in the PMG-ARDL regression results. The negative correlation between health expenditures and life expectancy suggests healthcare system reform to ensure that spending improves healthcare outcomes. The findings also suggest that public health should be considered in the efforts to boost GDP growth. Investment in Internet infrastructure and mobile networks is also necessary to improve healthcare access in G7 nations. Management of health budgets should include an output-oriented assessment of spending, and policymaking should support economic growth in a way that promotes public health.